The role of involved field irradiation versus elective nodal irradiation in definitive radiotherapy or chemoradiotherapy for esophageal cancer- a systematic review and meta-analysis - Wang, Hesong; Song, Chunyang; Zhao, Xiaohan; Deng, Wenzhao; Shen, Wenbin (Frontiers in Oncology, 2022)
Objective: This study aimed to analyze whether involved field irradiation (IFI) is associated with improving survival outcomes and reducing adverse events compared with elective nodal irradiation (ENI) in patients of esophageal cancer who underwent definitive radiotherapy or chemoradiotherapy. Summary Background Data: Radiotherapy plays an important role for not surgery patients. However, the role of radiation target size is still uncertain. Methods: We searched Web of Science, Embase, PubMed, and Cochrane Central for English and non-English publications comparing esophageal cancer patients who received radiotherapy with IFI with those with ENI. Primary outcomes included overall survival (OS) and adverse events related to radiotherapy. The risk of bias was assessed using the Cochrane Risk of Bias tool for randomized studies and the Newcastle-Ottawa Scale and Agency for Healthcare Research and Quality Standard for non-randomized studies. We evaluated the certainty of evidence by Grading of Recommendations, Assessment, Development, and Evaluation. Results: Totally, 23 studies with 4120 patients were included. IFI group demonstrated significant improvement in the OS rates at 5 years, but not at 1, 2, and 3 years, compared with the ENI group (pooled Risk Ratio [RR], 0.78; 95% confidence interval [CI], 0.68–0.90; P = 0.0004; high certainty). In addition, IFI demonstrated a significant decrease in the incidence of grade ≥2 acute esophagitis (AE) (pooled RR, 0.79; 95% CI, 0.69–0.90; P = 0.0005; high certainty) and grade ≥3 AE (pooled RR, 0.51; 95% CI, 0.38–0.69; P < 0.00001; high certainty) compared with ENI, but not in the incidence of grades ≥3 acute pneumonia, late esophagitis, and late pneumonia. Conclusions: Compared to ENI, IFI demonstrated significant improvement in OS at 5 years. The addition of intensity-modulated radiotherapy (IMRT) to IFI increased the 5-year OS; however, similar results were not observed with the addition of three-dimensional conformal radiotherapy to IFI and ENI. Furthermore, IFI demonstrated a significant decrease in grade ≥2 and grade ≥3 AE, while IMRT demonstrated no difference in the incidence of grade ≥3 AE. IFI and ENI do not differ in the incidence of grades ≥3 acute pneumonia, late esophagitis, and late pneumonia.